Career Choices of Students from Broken Home Families - Miftahul Rahmi; Rila Rahma Mulyani; Rahmawati Wae (Global Action and Education for Society, 2026)
This research is motivated by the presence of students from broken home families who lack confidence in their career choices and are not yet able to develop their careers. This study aims to understand the career choices of students from broken home families from the following aspects: 1) self-confidence in career choices, 2) responsibility in career choices, 3) guidance and self-development, 4) perseverance, creativity, and initiative, 5) desire to independently pursue their career choices. This type of research uses qualitative descriptive methods with 2 key informants, SH and KAR. Additional informants include 4 people, EDF, ALN, W, and N. Data collection techniques involve interviews, and the analysis technique includes data reduction, data presentation, and drawing conclusions. The results of this study show differences between the two informants, SH and KAR, in choosing a career: 1) SH students are confident in choosing a career because they already know their interests and talents. Informant KAR shows relatively low confidence because they do not know their interests and talents. 2) SH students have a responsible attitude and effort in the learning process, both in theory and practice, while KAR students tend to be lazy during practice and do not focus on their chosen field. 3) SH students can identify their potential in the automotive field and are able to develop their potential, while KAR students are still confused about their potential despite attending a career-focused school. 4) SH students have not yet applied the three aspects of diligence, creativity, and initiative in their career choice process, but they have applied these three aspects in their learning process. KAR students do not apply these three aspects in their learning process. 5) SH students have internal motivation to choose a career, while KAR students lack internal motivation. The results of this study indicate that students from broken home families tend to face obstacles in making career choices. Therefore, it is recommended that the school, particularly the guidance counselors, provide more intensive and directed career counseling services.